Concurrent effects of recycled aggregates and polypropylene fibers on workability and key strength properties of self-consolidating concrete. (28th February 2019) - Matar, Pierre; Assaad, Joseph J.
Highlights: Concurrent effects of recycled aggregates and polypropylene fibers on internal friction. Quantifying the magnitude of internal friction on workability of SCC. Changes in SCC rheological properties and passing ability due to RAC and PPF. Assessing key strength properties due to RAC and PPF. Abstract: The concurrent effects of recycled concrete aggregate (RCA) and polypropylene fibers (PPF) on workability of self-consolidating concrete (SCC) are not quantified in literature. Different SCC series containing 25% to 100% RCA and 0.25% to 1.75% PPF are investigated in this study; the water-to-binder ratio varied from 0.38 to 0.5, while high-range water reducer adjusted to maintain slump flow at 700 ± 25 mm. Flowability, cohesiveness, passing ability, and segregation resistance were evaluated and compared with the limitations specified by the European Guidelines for SCC. Test results have shown that SCC rheological properties and passing ability dramatically curtailed with PPF inclusions, especially when mixtures are proportioned with higher RCA replacement rates. This was attributed to combined effects of fiber additions that hinder the cement matrix deformation together with increased RCA surface roughness that accentuates internal friction and resistance to flow. Mixtures containing increased RCA and PPF concentrations exhibited better stability, reflected by reduced aggregate segregation. Series of regression models were proposed to predict the coupled effects of RCA and PPF additions on SCC workability responses.